2019
DOI: 10.1093/eurpub/ckz090
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with mental health treatment among patients with a non-Western migrant background: a survey in a Danish specialized outpatient mental health clinic

Abstract: Background Global migration increases ethnic and cultural diversity and demands mental health services to adapt to provide all patients with equal access to good quality care. Patient satisfaction surveys can inform this service delivery, thus we explored patient satisfaction among non-Western migrants receiving treatment in a Danish specialized outpatient mental health clinic [Competence Centre for Transcultural Psychiatry (CTP)]. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…In the course of shared decision-making, it appears to be beneficial that the physician recommends and discusses in-depth diagnosis and treatment of MDs with the patient after a positive MD screening. The shared decision on MD treatment can also increase adherence, which in turn can improve patient satisfaction and quality of life [35].…”
Section: Quality Of Life and Patient Satisfactionmentioning
confidence: 99%
“…In the course of shared decision-making, it appears to be beneficial that the physician recommends and discusses in-depth diagnosis and treatment of MDs with the patient after a positive MD screening. The shared decision on MD treatment can also increase adherence, which in turn can improve patient satisfaction and quality of life [35].…”
Section: Quality Of Life and Patient Satisfactionmentioning
confidence: 99%
“…In this study, the sample of more than 7,000 patients across 5 European countries was large and provided considerable statistical power to adjust differences between migrants and non-migrants for potentially confounding characteristics of the patients. This is essential for such a comparison since migrants and non-migrants differ in a range of socio-demographic and clinical characteristics, and these characteristics need to be taken into account in a meaningful statistical analysis [5,7,13,24]. Patients were studied in routine care and outcomes were not influenced by the research process.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Yet, there is a lack of large-scale research on whether outcomes of psychiatric treatments are truly different for migrant groups, and this applies to objective outcomes as well as patients' subjective appraisal of it [12]. Patient satisfaction is known to be a key indicator of quality of care [13,14], and is described as "an expression of the gap between the expected and the perceived quality of a service [11, page 69]. Higher levels of satisfaction with inpatient care have been shown to be associated with lower readmission rates to hospital and lower disability levels within 1 year [15][16][17], better adherence to medication and treatment, and a reduction in psychotic symptoms up to three 3 years later [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…HSR), their satisfaction with, and their experiences of the health system [11]. In high-income countries, several studies have described the experiences and perceptions of migrants of the health care systems in their host countries [12][13][14][15][16][17][18][19][20]. A 2010 review of migrants using health care services in high-income countries demonstrated negative associations between patient satisfaction scores and gender, age and education levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK (UK), studies have found that gypsies, travellers and minority ethnic groups experienced high levels of inequalities in the access and/or the quality of care they received in the public healthcare system [15,16]. In Germany [17,18] and Denmark [19], studies found that migrant patients' satisfaction with health care services were influenced by communication by, and cultural sensitivity of, health care providers. A 2016 qualitative study that explored HIV-positive migrants' experiences in the Swedish health care system found that they appreciated access to free antiretroviral therapy, but felt discrimination in health care settings outside of the infectious diseases clinics [21].…”
Section: Introductionmentioning
confidence: 99%